Lay-Off Seniority Clause and Management Rights

(untitled) (Département des relations industrielles de l’Université Laval, 1959)
SummaryBy the majority, where there is no specification on the procedure to be followed in cases of lay-offing employees with equal seniority the employee with the greater number of days of service should have the preference.